Managing English for frontliners (EFF) in “Darussalam” community-based job training center - Naeli Rosyidah; Enjang Burhanudin Yusuf; Yasinta Wulandari (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2026)
The problems of unemployment rate because of lack of access to vocational trainings, especially English language trainings, drove the Indonesian Ministry of Manpower established community-based Job Training Centers. One such community-based Job Training Center (JTC) established is Darussalam JTC. This study aims to examine the implementation of the effective management of the English for Frontliners (EFF) course at Darussalam community-based Job Training Center (JTC). A qualitative research approach with a case study design was employed, utilizing documentation analysis and interviews. The findings reveal that the course had Government-driven preparation system with proposal submission, cooperation agreement, instructor training and certification, curriculum based on the national curriculum standards, and transparent trainee recruitment and registration. The course, then, was implemented with standards-based implementation with Pesantren value integration, and dual evaluation system with tests and report.